The reactionary bourgeoisie in Lithuanian education policy in terms of professional training issues in elementary school (1919-1940 curricula analysis) - Mikėnas, V. (Psichologija, 1965)
An analysis of the bourgeois Lithuanian primary school curriculum professional training issues reaffirmed that the bourgeoisie has neglected its management during professional training, and rather tried to use it to maintain class inequality. While the bourgeois government diverted the full government apparatus and nationalist ideology against the Marxist-Leninist ideas of professional training, persecuted and tried to distort them in every way, they remained alive and functioned for the school and students. The Lithuanian Communist Party-led revolutionary movement and the united professional schools in the USSR experience promoted professional training progressive movement in Lithuania. Professional training elements were formulated on this basis: introduction to the world of work, working people’s activities, and rudimentary work skills positively acted upon training process as well as being a positive source of scientific outlook in bourgeois Lithuania. Thus the ruling bourgeoisie attempts to suppress the ideas of progressive professional training were fruitless, and when the anti-fascist movement intensified and Lithuania was ripe for revolution, fascist leaders lost their balance and in order to distract the attention of progressive teachers from the analysis of the Soviet school and scientific work and teaching, they began to feverishly change programs (1936, 1939, 1940). This testifies to the weakening of the position of the bourgeoisie, the workers fighting for their rights are gaining strength, which led to the overthrow of the bourgeois government and the restoration of Soviet power in Lithuania, so all the conditions emerged for deployment of science-based professional education in schools.